Atrioventricular conduction in PM recipients after transcatheter aortic valve implantation: Implications using Wenckebach point measurement - Pelargonio, Gemma; Scacciavillani, Roberto; Donisi, Luca; Narducci, Maria Lucia; Aurigemma, Cristina; Pinnacchio, Gaetano; Bencardino, Gianluigi; Perna, Francesco; Spera, Francesco Raffaele; Comerci, Gianluca; Ruscio, Eleonora; Romagnoli, Enrico; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Atrioventricular (AV) conduction disturbances requiring permanent pacemaker implantation (PPI) are a common complication after transcatheter aortic valve implantation (TAVI). However, a significant proportion of patients might recover AV conduction at follow-up. Objectives The aim of our study was to evaluate the recovery of AV conduction by determination through Wenckebach point in patients with PPI and therefore identify patients who could benefit from device reprogramming to avoid unnecessary RV pacing. Methods We enrolled 43 patients that underwent PM implantation after TAVI at our Department from January 2018 to January 2021. PM interrogation was performed at follow-up and patients with native spontaneous rhythm were further assessed for AV conduction through WP determination. Results A total of 43 patients requiring a PM represented the final study population, divided in patients with severely impaired AV conduction (no spontaneous valid rhythm or WP < 100; 26) and patients with valid AV conduction (WP ≥ 100; 17). In the first group patients had a significantly higher number of intraprocedural atrioventricular block (AVB) (20 vs. 1, p < 0.005), showed a significant higher implantation depth in LVOT (7.7 ± 2.2 vs. 4.4 ± 1.1, p < 0.05) and lower ΔMSID (−0.28 ± 3 vs. −3.94 ± 2, p < 0.05). Conclusion AV conduction may recover in a significant proportion of patients. In our study, valve implantation depth in the LVOT and intraprocedural AV block are associated with severely impaired AV conduction. Regular PM interrogation and reprogramming are required to avoid unnecessary permanent right ventricular stimulation in patients with AV conduction recovery.